Filament winding machine control using B-spline interpolation - Haq, Shaiq A. (1994)
Filament winding is a process for the placement of reinforcement fibres on to a rotating surface in a specified geometric pattern. A conventional straight line interpolation controller is not very appropriate for filament winding because the fibre pay-out-eye is at some distance away from the mandrel surface and its movement from one point to another may disturb the position of previously laid fibre on the mandrel. Filament winding demands a controller which can produce fast and smooth carriage movements, and have a path-anticipation capability so that while moving around curves the effect of pay-out-eye movement on previous fibre positions is minimised. This problem can be overcome by using an interpolation technique which determines the pay-out-eye path by considering more than two data points, and whose profile is continuous in nature up to its second derivative. In this project an IDM PC based filament winding controller, using B-spline interpolation technique, is developed. To test the performance of the controller a 3-axis CNC filament winding machine was designed and manufactured. For optimum performance, emphasis was given to the low inertia of the machine carriage, while at the same time maintaining the system's structural stiffness. To reduce the machine carriage weight, the DC servomotors were installed on the machine's frame, instead of the carriage, and a timing belt arrangement was used for power transmission. The controller's electronic hardware was assembled using servo amplifiers, DAC cards, and a purpose built optical encoder interface card. The controller software was developed using TURBO C++ as the main programming language, whereas the hardware interface routines were written in Assembly Language. Problems of winding path deviation as a result of B-spline approximation were tackled using knowledge based programming techniques. The results showed a considerable improvement in winding speed and less fibre slippage in the case of non-geodesic winding patterns, resulting in higher accuracy of fibre placement on the mandrel.